The IDIP framework for assessing protein function and its application to the prion protein. (6th May 2021) - Schmitt‐Ulms, Gerold; Mehrabian, Mohadeseh; Williams, Declan; Ehsani, Sepehr
ABSTRACT: The quest to determine the function of a protein can represent a profound challenge. Although this task is the mandate of countless research groups, a general framework for how it can be approached is conspicuously lacking. Moreover, even expectations for when the function of a protein can be considered to be 'known' are not well defined. In this review, we begin by introducing concepts pertinent to the challenge of protein function assignments. We then propose a framework for inferring a protein's function from four data categories: 'inheritance', 'distribution', 'interactions' and 'phenotypes' (IDIP). We document that the functions of proteins emerge at the intersection of inferences drawn from these data categories and emphasise the benefit of considering them in an evolutionary context. We then apply this approach to the cellular prion protein (PrP C ), well known for its central role in prion diseases, whose function continues to be considered elusive by many investigators. We document that available data converge on the conclusion that the function of the prion protein is to control a critical post‐translational modification of the neural cell adhesion molecule in the context of epithelial‐to‐mesenchymal transition and related plasticity programmes. Finally, we argue that this proposed function of PrP C has already passed the test of time and is concordant with the IDIP framework in a way that other functions considered for this protein fail to achieve. We anticipate that the IDIP framework and the concepts analysed herein will aid the investigation of other proteins whose primary functional assignments have thus far been intractable.